Antimicrobial, Anti-Inflammatory and Antioxidant Activities of Polyoxygenated Chalcones - Montoya-Kunsting, M; Mascayano-Collado, C; Vasquez-Martinez, y; Cortez-San Martin, M; Mejías-Medina, S; Cabezas-Gómez, F; Torrent-Farias, C (Sociedade Brasileira de Quimica, 2019)
It was synthesized nine polyoxygenated chalcones with a potential and safe use as antioxidant, antimicrobial and anti-inflammatory therapies. Chalcones obtained by Claisen-Schmidt condensation were studied as antioxidant, inhibitors of human 5-lipoxygenase, antifungal, antibacterial and antibiotic resistance modifiers. Two chalcones with catecholic moieties were able to strongly decrease the minimum inhibitory concentration (MIC) of methicillin against methicillin-resistant Staphylococcus aureus, increase the antiradical activity and significantly inhibit the human 5-lipoxygenase. Only one of these chalcones was active synergistically with methicillin. Chalcones with methoxyl substituents at different positions displayed the best activities against Cryptococcus neoformans. Only one chalcone showed good activity against the plant pathogenic bacteria Pseudomonas syringae whose half maximal inhibitory concentration (IC50) value (2.5 µg mL-1) was similar to that observed with the antibiotic streptomycin (2.9 µg mL-1). These simple chalcones have safe potential uses in antioxidant, antimicrobial and anti-inflammatory therapies. ©2019 Sociedade Brasileira de Química.